Validation of a new HPLC‐UV method for determination of the antibiotic linezolid in human plasma and in bronchoalveolar lavage. (1st July 2013) - Fortuna, Serena; De Pascale, Gennaro; Ragazzoni, Enzo; Antonelli, Massimo; Navarra, Pierluigi
ABSTRACT A rapid and selective HPLC‐UV method was developed for the quantification of linezolid (LNZ) in human plasma and bronchoalveolar lavage (BAL) at the concentrations associated with therapy. Plasma samples were extracted by solid‐phase extraction followed by evaporation to dryness and reconstitution in mobile phase solution. The chromatographic separation was carried out on a C18 column with an isocratic mobile phase consisting of dihydrogen phosphate buffer 50 mm (pH 3.5) and acetonitrile (60:40 v/v). The detection was performed using a photodiode array. Under these conditions, a single chromatographic run could be completed within 12 min. The method was validated by estimating the precision and the accuracy for inter‐ and intra‐day analysis in the concentration range of 25–25600 ng/mL. The method was linear over the investigated range with all the correlation coefficients R > 0.999. The intra‐ and inter‐day precision was within 8.90% and the accuracy ranged from −4.76 to +5.20%. This rapid and sensitive method was fully validated and could be applied to pharmacokinetic study for the determination of LNZ levels in human plasma and BAL samples. Copyright © 2013 John Wiley & Sons, Ltd.